Effect of the regulation of freshwater inflow on the physical-chemical characteristics of water and on the aquatic macrofauna in the Guadalquivir estuary - Francisco Baldo; José A Cuesta; Carlos Fernández-Delgado; Pilar Drake (Ciencias Marinas, 2005)
From June 1998 to May 1999, the water temperature, salinity and turbidity, together with the macrofaunal (nekton and hyperbenthos) abundance, biomass and number of species, were estimated in the Guadalquivir estauary at five sampling stations (8, 20, 30, 40 and 50 km from the river mouth). Samples were taken from an anchored boat by using nets with a 1-mm mesh. There was a horizontal salinity gradient along the estuary: monthly mean salinities ranged from 17 to 27 at the outermost sampling station, whilst salinity was rarely higher than 4 in the inner estuary. Water temperature was homogenous throughout the estuary, with maximum values in summer (28ºC) and minimum values in winter (10ºC). Turbidity was also relatively homogenous throughout the estuary, with a maximum in winter (362 NTU) and a minimum in summer (10 NTU). Maximum turbidity occurred in the zone where seawater and freshwater merge. Results of stepwise multiple regression analysis indicated that both the distance to the river mouth and the freshwater input (in the previous month) from the Alcalá del Río dam (110 km from the river mouth) explained 70% of the variance in salinity, but that the freshwater input only explained 17% of the variance respecin water temperature and turbidity. Salinity explained 50% of the variance in the number of species, whereas salinity and temperature were the environmental variables that controlled the macrofaunal abundance and biomass. Salinity and temperature together explained 75% and 71% of the variance for nekton abundance and biomass, respectively, and 54% and 48% of the variance for the abundance and biomass of hyperbenthos, respectively. Salinity was, in all cases, the individual variable that explained the highest portion of variance.